2016
DOI: 10.7860/jcdr/2016/15867.7060
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines and their Relation to Endothelial Dysfunction in Patients with Chronic Kidney Disease

Abstract: The present study demonstrates that adipokine levels are altered from initial to final stages of CKD due to renal dysfunction which in association with an exaggerated inflammation may contribute to the ED and CV events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…However, Malyszko et al 39 and Adamczak et al 44 reported increased levels of adiponectin in HD patients compared with those of the CRF or KT patient groups and KTR or control groups, respectively. In another study, Ambarkar et al 45 investigated adiponectin levels of CRF patients and reported reduced levels of adiponectin in those patients compared to the healthy subjects; however, those authors found an increment in adiponectin levels as the stage of the CRF advanced and suggested that the increment might be related to the progressed kidney dysfunction. Several studies reported a negative correlation between adiponectin and CRP levels in patients with Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…However, Malyszko et al 39 and Adamczak et al 44 reported increased levels of adiponectin in HD patients compared with those of the CRF or KT patient groups and KTR or control groups, respectively. In another study, Ambarkar et al 45 investigated adiponectin levels of CRF patients and reported reduced levels of adiponectin in those patients compared to the healthy subjects; however, those authors found an increment in adiponectin levels as the stage of the CRF advanced and suggested that the increment might be related to the progressed kidney dysfunction. Several studies reported a negative correlation between adiponectin and CRP levels in patients with Table 3.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 , 18 , 19 , 20 , 21 The supporting data include the observation that CKD patients have elevated NEFA concentrations, an independent predictor of all-cause and cardiovascular death. 21 Furthermore, CKD patients have perturbed circulating adipokine concentrations 18 , 20 and increased systemic inflammation that correlates with fat mass. 16 Indeed, visceral fat mass in peritoneal dialysis patients is an independent predictor of vessel dysfunction and therefore a risk factor for CVD.…”
mentioning
confidence: 93%
“…On the other hand, since more than 90% of filtered urate is reabsorbed by the kidney, renal damage could affect this complex process, and in this context LPT may play a crucial role. Indeed, LPT may unfavourably contribute to the decline in renal function [7] both by a direct effect of nephron disruption and by an indirect effect though an inflammation status and a higher insulin resistance [20,21]. High LPT is involved in the promotion and progression of endothelial dysfunction and vascular damage, in particular it exerts the effects through glomerular endothelial cell proliferation, increased synthesis of collagen and hypertrophy of the mesangium cells [20,21], increased serum levels of adhesion molecules [20] and contributing to vascular remodelling [22].…”
Section: Introductionmentioning
confidence: 99%